(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this in vitro study was to evaluate the marginal interfaces between tooth structure and the retro-filling materials. Sixty teeth were divided into six groups of ten for each. The teeth were instrumented to a minimum of size no. 45 k-file, obturated with gutta-percha, resected perpendicular to their long axes and prepared to receive a retro-filling. The teeth were filled with amalgam, resin-modified GIC or light-cured composite resin. Each filling material was either applied with dentin adhesive or without dentin adhesive. Photomicrographs were made & examined by four evaluators. Statistical analysis of the results revealed that the composite resin had better marginal adaptation than the amalgam & the glass ionomer cement, but the difference was non significant (p>0.05). In addition, the non-adhesive groups together had less marginal adaptation than the other groups and the difference was significant (p<0.05). Composite resin retro-filling material had better marginal adaptation than other materials used and the dentin adhesive may have effect on the quality of the adaptation.